2011
DOI: 10.1021/ac1029242
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Study of Iron Gall Ink Impregnated Paper Degradation under Various Oxygen and Humidity Conditions: Time-Dependent Monitoring by Viscosity and X-ray Absorption Near-Edge Spectrometry Measurements

Abstract: Many western manuscripts were written using iron gall inks. These inks can damage the paper via two major mechanisms: (a) acid hydrolysis, enhanced by humidity, and (b) oxidative depolymerization provoked by the presence of oxygen and free iron(II) ions. The degradation of unsized Whatman paper impregnated with different combinations of iron sulfate, gallic acid, and gum arabic was studied at room temperature in order to assess the relative importance of each mechanism. The samples were stored in various envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 21 publications
3
51
0
4
Order By: Relevance
“…Anyway, whatever the cause of acidity, the low pH values of our samples give substantial reasons to suspect acid-catalysed hydrolysis as the main cause of chain scission. This first interpretation does not stand when examining paper behaviour in further details: in previous work [26], ink impregnated papers were conditioned in anoxia and their degradation was delayed. Moreover, papers impregnated with pure gallic acid did not show significant depolymerization at ambient temperature despite showing a low pH value (3.6).…”
Section: Kinetic Approach Of Mechanical Decaymentioning
confidence: 94%
See 3 more Smart Citations
“…Anyway, whatever the cause of acidity, the low pH values of our samples give substantial reasons to suspect acid-catalysed hydrolysis as the main cause of chain scission. This first interpretation does not stand when examining paper behaviour in further details: in previous work [26], ink impregnated papers were conditioned in anoxia and their degradation was delayed. Moreover, papers impregnated with pure gallic acid did not show significant depolymerization at ambient temperature despite showing a low pH value (3.6).…”
Section: Kinetic Approach Of Mechanical Decaymentioning
confidence: 94%
“…In a previous work, using anoxic and aerated ageing conditions, we showed that the combination of oxygen and iron was a key factor for cellulose chain breaking occurring in acidic conditions (pH 3-4) [26]. Therefore, paper degradation induced by IGI would be predominantly driven by oxidative mechanisms involving iron or cellulose.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, they participate to the oxidative degradation of cellulose [20,21] and increase the concentration of hydroxyl radical generated upon light exposure [18]. As well, iron influences the degradation of cellulose in iron gall-ink manuscripts [22]. Therefore, the participation of Prussian blue to the degradation process of the fibers cannot be ruled out, to the contrary, and would be interesting to investigate.…”
Section: Prussian Blue and Textile Substrate Act As A Redox Systemmentioning
confidence: 99%